Coordination Cluster Analogues of the High‐Spin [Mn19] System with Functionalized 2, 6‐Bis(hydroxymethyl)phenol Ligands. Issue 26 (24th July 2014) - Mameri, Samir; Ako, Ayuk M.; Yesil, Fatma; Hibert, Marcel; Lan, Yanhua; Anson, Christopher E.; Powell, Annie K.
Abstract: A series of 2, 6‐bis(hydroxymethyl)‐4‐R‐phenol ligands (H3 L R ; R = H, F, Cl, Br, I, Ph, NH2, NO2, SMe) have either been newly synthesized or the existing syntheses have been significantly improved to investigate ligand‐functionalized analogues of the previously published coordination cluster [Mn III 12 Mn II 7 (μ4 ‐O)8 (μ3 ‐N3 )8 (HL Me )12 (MeCN)6 ]Cl2 · 10MeOH· MeCN (1 ) with S = 83/2. The crystal structures and magnetic properties of three such Mn19 clusters, namely, [Mn III 12 Mn II 7 (μ4 ‐O)8 (HL H )12 (μ3 ‐Cl)7 (μ3 ‐OMe)(MeOH)6 ]Cl2 · 16H2 O· 10MeOH· MeCN (3 ), [Mn III 12 Mn II 7 (μ4 ‐O)8 (HL I )12 (μ3 ‐N3 )8 (MeOH)6 ](O2 CH)2 · 16MeOH· 10MeCN (4 ) and [Mn III 12 Mn II 7 (μ4 ‐O)8 (μ3 ‐Cl)7.7 (μ3 ‐OMe)0.3 (HL SMe )12 (MeOH)6 ]Cl2 · 27MeOH (5 ) are reported and compared to those of the parent cluster. When these ligands are functionalized with substituents of moderate electronegativity, it is possible to synthesize Mn19 analogues; however, when such ligands bear highly electron‐donating (amino) or ‐withdrawing (nitro) substituents, the Mn19 analogues are no longer accessible. The Mn19 cluster framework is both magnetically and structurally robust with respect to the electron‐donor/acceptor characteristics of the ligand substituent; therefore, the Mn19 system is an excellent platform for peripheral chemical engineering. Abstract : The robustness of the inorganic Mn III 12 Mn II 7 (μ4 ‐O)8 core of Mn19 systems with variously functionalized encapsulating ligands is demonstrated by the invariance of the record S = 83/2 spin state. Chemical modification aimed towards attaching the molecule to various substrates does not interfere with the electronic structure.